Requirement of a properly acylated beta(1-6)-D-glucosamine disaccharide bisphosphate structure for efficient manifestation of full endotoxic and associated bioactivities of lipid A. - Takahashi, I (1987)
Several synthetic acylated glucosamine monophosphates, with structures corresponding to the nonreducing or reducing moiety of the lipid A of the Escherichia coli or Salmonella minnesota type, and a synthetic compound corresponding to a biosynthetic disaccharide lipid A precursor (designated Ia or IVA) were examined for their endotoxic and related bioactivities in comparison with those of the synthetic and bacterial parent molecules, i.e., acylated beta(1-6)-D-glucosamine disaccharide bisphosphates. Some of the test monosaccharide compounds were definitely active in most of the in vitro assays. Their activities, except for complement activation, however, were weaker than those of the reference compounds, synthetic and bacterial acylated disaccharide bisphosphates. The differences between the test monosaccharide and disaccharide compounds were much more apparent in in vivo assays, in which the test acylated glucosamine monophosphates were scarcely active, though some test compounds exhibited weak lethal toxicity in galactosamine-loaded mice and were weakly active in pyrogenicity, immunoadjuvant activity, and possible tumor necrosis factor and alpha and beta interferon-inducing ability in Mycobacterium bovis BCG- and Propionibacterium acnes-primed mice, respectively. Mixture at an equimolar ratio of acyl glucosamine monophosphates, each of which has the structure of the reducing or nonreducing moiety of the reference disaccharide compound, did not restore the endotoxic or associated bioactivities of the corresponding parent molecules. No essential differences in bioactivity were noted between synthetic and bacterial monosaccharide compounds, i.e., lipid X, whose structure corresponds to the reducing moiety of E. coli-type lipid A.